Transition in the Context of Inclusive Education: Opinions of Preschool Teachers and Professional Associates - Mirjana M. Nikolić; Isidora B. Korać; Milijana B. Lazarević (Inovacije u Nastavi, 2020)
Given that transition from one level of education to another can be especially sensitive for children with disabilities, the aim of the research is to determine the opinion of preschool teachers and professional associates (members of the Professional Team for Inclusive Education) on the current practice of transition from preschool institutions to primary school with regard to this group of children. In the first phase of the research, a sample of 234 preschool teachers from eight preschool institutions in four cities was given a close-ended questionnaire created specifically for the purpose of this research. In the second phase, focus-group interviews were conducted with the members of the Professional Team for Inclusive Education in two preschool institutions. The majority of the respondents believe that the transition between preschool institution and primary school in working with children with disabilities is not realised. In their opinion, the main obstacles to this transition are: insufficient involvement and support of professional associates, inconsistency of the methods applied by preschool and primary school teachers respectively, the lack of interest in the previous development of children with disabilities, the lack of a binding legislative act which would define the process of transition, and the insufficient competencies of preschool teachers for working with the pedagogical documents. The authors of the paper propose the enactment of a legislative act on transition that would clearly define the roles and duties of all participants in this process.